2002
DOI: 10.1103/physrevlett.88.106403
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Spin and Orbital Degrees of Freedom inKCuF3

Abstract: We present the results of resonant x-ray scattering experiments on KCuF3. Structurally forbidden reflections, corresponding to magnetic and 3d-orbital long-range order, have been observed. Integrated intensities have been measured as a function of incident energy, polarization, azimuthal angle, and temperature. The results give evidence for a strong coupling between orbital and spin degrees of freedom. The interplay between magnetic and orbital order parameters is revealed by the temperature dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 23 publications
4
82
0
Order By: Relevance
“…LDA+ U calculations 55,56 have indicated that such purely electronic interactions would already drive the instability towards the C-type OO ͑C-OO͒ phase, with alternating orbitals in the ab planes, and repeated orbitals along the c axis, which induces FM spin exchange in the ab planes, and strong AF exchange between the planes. Experimentally, this OO sets in below the structural transition at T s ϳ 800 K, 51 i.e., at much higher temperature than the characteristic energy scale of the magnetic excitations, 57 suggesting that the JT effect plays an important role in this instability. This observation is consistent with the large difference between T s and the Néel temperature T N ϳ 38 K, 52 the latter being controlled by the magnetic part of the superexchange, and thus the orbital correlations decouple from the spin-spin correlations.…”
Section: B Spin Exchange Constants and Optical Intensitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…LDA+ U calculations 55,56 have indicated that such purely electronic interactions would already drive the instability towards the C-type OO ͑C-OO͒ phase, with alternating orbitals in the ab planes, and repeated orbitals along the c axis, which induces FM spin exchange in the ab planes, and strong AF exchange between the planes. Experimentally, this OO sets in below the structural transition at T s ϳ 800 K, 51 i.e., at much higher temperature than the characteristic energy scale of the magnetic excitations, 57 suggesting that the JT effect plays an important role in this instability. This observation is consistent with the large difference between T s and the Néel temperature T N ϳ 38 K, 52 the latter being controlled by the magnetic part of the superexchange, and thus the orbital correlations decouple from the spin-spin correlations.…”
Section: B Spin Exchange Constants and Optical Intensitiesmentioning
confidence: 99%
“…4,19 Orbital order occurs in KCuF 3 below the structural transition at T s ϳ 800 K. At T Ͻ T s the structure is tetragonal, with longer Cu-Cu distances within the ab planes ͑d ab = 8.28 Å͒ than along the c axis ͑d c = 7.85 Å͒, 49 which favors strong AF interactions along the c axis. Below the magnetic transition at T N Ӎ 38 K, long-range magnetic order of A type sets in, 50,51 and the ordered moment is 0 = 0.48 B . 52 The superexchange between the Cu 2+ ions in KCuF 3 , Fig.…”
Section: ͑213͒mentioning
confidence: 99%
“…Moreover, the electronic and structural properties of KCuF 3 have been recently reexamined by means of LDA+U molecular-dynamic simulations, indicating a possible symmetry change and challenging the original assignment of tetragonal symmetry. 44 This symmetry change seems to allow for a better understanding of Raman, 46 electronic paramagnetic resonance, 47,48 and x-ray resonant scattering 49 properties at T ≈ T N . However, the details of this distortion have not been fully resolved yet.…”
Section: Application To Kcufmentioning
confidence: 99%
“…Reported resonant enhancements at transition metal K edges of magnetic scattering intensities were typically very small and often broad (see, e.g., Refs. 34,35,36,37,38), compared to the substantial enhancements often observed at rare earth L edges (see for example Refs. 29,30,31,32).…”
mentioning
confidence: 99%